Analisis Manajemen Desa Terhadap Pembangunan - Karolus W. Rato; Lidia Ambu Kaka; Adriana Ghadi; Marianus Putra Bili; Febrianti H.Hangga (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Problems In development, village communities still have very significant problems. First, in terms of improvements, the improvements are because they are included in urban areas, while in general, our nation Indonesia, is still covered by rural areas. At that time, in the middle of the government. The New Order, various arrangements and programs for the improvement of the province were prepared, but it was clearly ready to see that the socio-economic conditions of rural communities were still very far from what was expected. The purpose of this research is to find out what the village government does in village management for development. To find out the factors that affect village management. methods used in the research, research results, conclusions, suggestions, and research implications.